Photometric and spectroscopic study of low mass embedded star clusters in reflection nebulae - Soares, J. B. (2005)
An analysis of the candidate embedded stellar systems in the reflection nebulae vdBH-RN 26, vdBH-RN} 38, vdBH-RN} 53a, GGD 20, ESO 95-RN 18 and NGC 6595 is presented. Optical spectroscopic data from CASLEO (Argentina) in conjunction with near infrared photometry from the 2MASS Point Source Catalogue were employed. The analysis is based on source surface density, colour-colour and colour-magnitude diagrams together with theoretical pre-main sequence isochrones. We take into account the field population affecting the analysis by carrying out a statistical subtraction. The fundamental parameters for the stellar systems were derived. The resulting ages are in the range 1-4 Myr and the objects are dominated by pre-main sequence stars. The observed masses locked in the clusters are less than 25 Msun. The studied systems have no stars of spectral types earlier than B, indicating that star clusters do not necessarily evolve through an HII region phase. The relatively small locked mass combined with the fact that they are not numerous in catalogues suggests that these low mass clusters are not important donors of stars to the field populations.